Reassessment of T Lymphocytes Crossmatches Results Prediction With Luminex Class I Single Antigen Flow Beads Assay. Issue 3 (March 2017) - Visentin, Jonathan; Bachelet, Thomas; Borg, Cécile; Franchini, Nicolas; Nong, Thoa; Lee, Jar-How; Couzi, Lionel; Merville, Pierre; Guidicelli, Gwendaline; Taupin, Jean-Luc
Abstract : Background: In virtual crossmatch (XM) strategies, a correct anticipation of XM results is required for appropriately allocating organs. We reassessed the ability to predict T lymphocyte flow cytometry and complement dependent cytotoxicity XM results with the mean fluorescence intensity (MFI) in Luminex class I single antigen flow beads (SAFB) assay, after correction of complement interference and exclusion of antidenatured HLA antibodies. Methods: Among 432 XM with T lymphocytes (T-XM), 407 were analyzed after exclusion of antidenatured HLA antibodies. Only ethylenediaminetetraacetic acid-treated serum MFI was considered. Only 1 cellular target HLA antigen for the serum was expressed in 238 cases, 209 and 29 being heterozygous and homozygous for this antigen, respectively. For the remaining 169 cases, at least 2 antigens were recognized. Single antigen flow bead MFI thresholds allowing XM positivity to be predicted were calculated with receiver operating characteristic curves. Results: T-XM results were tightly associated with SAFB MFI values. Anti-HLA-A and anti-HLA-B antibodies behaved similarly. Prediction and sensitivity SAFB MFI thresholds were determined, respectively, assessing the highest sensitivity/specificity ratio and at least 95% sensitivity for predicting T-XM positivity. Both were slightly lower for HLA-B than for HLA-A, whereas anti-HLA-Cw antibodies induced random XM results. Both thresholds were only slightly diminished for homozygous and for multiple HLA targets, considering the immunodominant, but not the sum, of antibodies MFI. Conclusions: Antibodies against HLA-A, -B, or -Cw behave differently. A homozygous HLA target does not trigger a twice higher XM positivity. Multiple antibodies are better evaluated through the immunodominant DSA MFI than through the sum of DSA MFI. Abstract : In the present study, the authors assess the correlations between Luminex class I single antigen flow beads assay (MFI) and T cell crossmatches in kidney transplant recipients after correction for complement interference and anti-denatured HLA antibodies. Prediction is good for anti-HLA A, B but not C antibodies. The information given by the immunodominant DSA MFI is compared to the sum of various DSA MFIs. Supplemental digital content is available in the text.